Assessment of Antenatal Care Services regarding Iron deficiency anemia during pregnancy In Sudan - 2010 - AL- Any, Ban N.; AL Deen AL- Saied, Deyaa; Ubaid, Seeham M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Pregnancy is a crucial time to promote health thus good antenatal care can promote mother and new born health &links mother with formal health system with increasing chance of using a skilled attendant at birth while inadequate care during this time increases mortality & morbidity of mother & new born.Objectives: Assessment of Antenatal Care Services in relation with Iron deficiency anemia during pregnancy.Patients and Methods; A descriptive study was carried out in 12 health centers , which were chosen randomly in Behri area (part of Khartoum City) in Sudan that (300) available pregnant females in 3rd trimester were interviewed (using non probability convenience sampling) by using a questionnaire paper during the period between September– December2010.Results; The study revealed that most of females were educated & all of their husbands were educated, more than half of them were over thirty & 22% below fifteen , about quarter of them had history of previous abortion & had complications mostly hypertension .The prevalence of anemia was 60% , 40% had mild anemia (mean hemoglobin & S.D 10.18, ±0.51), C.I (10.58 –9.79) , p value